E-Modul Etnosains sebagai Media Literasi Sains di Sekolah Dasar - Shafira Cahyaning Putri; A.F. Suryaning Ati MZ; Linaria Arofatul Ilmi Uswatun Khasanah (Jurnal Tematik, 2026)
This study aims to develop an ethnoscience-based e-module to improve students' scientific literacy in Natural and Social Science learning for fifth-grade elementary school students. The background of the study lies in the low level of students' scientific literacy and the limited use of interactive digital learning media. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) for the topic “Sound and Its Properties.” The instruments used included material and design expert validation sheets, student response questionnaires, student activity observations, and scientific literacy tests (pretest and posttest). The results showed that the developed e-module had a very high level of validity, with an average score of 3.87 from material experts and 3.70 from design experts. The practicality of the e-module was in the "excellent" category, with student response scores of 4.5 (small group) and 4.6 (large group). Student activity increased from 4.4 to 4.7. The effectiveness test showed a significance value of 0.000 (p < 0.05) and an N-Gain of 51.95%, which falls into the moderate category. In conclusion, the ethnoscience-based e-module is effective as an innovative learning medium to improve scientific literacy among elementary school students. Keywords: e-module; ethnoscience; scientific literacy; IPAS; elementary school